Reactive Oxygen Species Play a Role in the Infection of the Necrotrophic Fungi, Rhizoctonia solani in Wheat - Foley, R.; Kidd, B.; Hane, James; Anderson, J.; Singh, K. (Public Library of Science, 2016)
Rhizoctonia solani is a nectrotrophic fungal pathogen that causes billions of dollars of damage to agriculture worldwide and infects a broad host range including wheat, rice, potato and legumes. In this study we identify wheat genes that are differentially expressed in response to the R. solani isolate, AG8, using microarray technology. A significant number of wheat genes identified in this screen were involved in reactive oxygen species (ROS) production and redox regulation. Levels of ROS species were increased in wheat root tissue following R. solani infection as determined by Nitro Blue Tetrazolium (NBT), 3,3'-diaminobenzidine (DAB) and titanium sulphate measurements. Pathogen/ROS related genes from R. solani were also tested for expression patterns upon wheat infection. TmpL, a R. solani gene homologous to a gene associated with ROS regulation in Alternaria brassicicola, and OAH, a R. solani gene homologous to oxaloacetate acetylhydrolase which has been shown to produce oxalic acid in Sclerotinia sclerotiorum, were highly induced in R. solani when infecting wheat. We speculate that the interplay between the wheat and R. solani ROS generating proteins may be important for determining the outcome of the wheat/R. solani interaction.